Respuesta :
Answer:
The substitution is
[tex]u = x ^ 4[/tex]
[tex]u ^ 2 -3u +2 = 0[/tex]
Step-by-step explanation:
We have the 8th degree polynomial equation
[tex]x ^ 8 - 3x^4 -+2 = 0[/tex]
To rewrite the equation as a quadratic function, take the common factor of the term x with the smallest exponent, in this case it is [tex]x ^ 4[/tex].
Now make a change of variable
[tex]u = x ^ 4[/tex].
So rewriting the equation in terms of u, we have:
[tex]u ^ 2 -3u +2 = 0[/tex]
Now the initial equation became a quadratic equation
Factoring is left:
[tex](u-2) (u-1) = 0[/tex]
[tex]u = 2[/tex] and [tex]u = 1[/tex]
[tex]x ^ 4 = 2[/tex] and [tex]x ^ 4 = 1[/tex]
Answer:
substitution should be p = x⁴
Step-by-step explanation:
It is given that,
x⁸ - 3x⁴ + 2 = 0
we can rewrite the equation,
(x⁴)² - 3x⁴ + 2 =0
To find the substitution
Here we can see that x⁴ is common in two terms of the given equation
we can substitute p instead of x⁴, the equation becomes,
p² - 3p +2 = 0
Therefore substitution should be used to rewrite x8 – 3x4 + 2 = 0 as a quadratic equation is p = x⁴